Distribution and pathogenicity of Colletotrichum species associated with mango anthracnose in Mexico - Tovar Pedraza, Juan Manuel (2020)
Mango anthracnose, caused by Colletotrichum spp., is the most significant disease of mango (Mangifera indica L.) in almost all production areas around the world. In Mexico, mango anthracnose has only been attributed to C. asianum and C. gloeosporioides. The aims of this study were to identify the Colletotrichum species associated with mango anthracnose symptoms in Mexico by phylogenetic inference using the ApMat marker, to determine the distribution of these species, and to test their pathogenicity and virulence on mango fruits. Surveys were carried out from 2010 to 2012 in 59 commercial orchards in the major mango growing states of Mexico, and a total of 118 isolates were obtained from leaves, twigs, and fruits with typical anthracnose symptoms. All isolates were tentatively identified in the C. gloeosporioides species complex based on morphological and cultural characteristics. The Bayesian inference phylogenetic tree generated with Apn2/MAT intergenic spacer sequences of 59 isolates (one per orchard) revealed that C. alienum, C. asianum, C. fructicola, C. siamense, and C. tropicale were associated with symptoms of mango anthracnose. In this study, C. alienum, C. fructicola, C. siamense, and C. tropicale are reported for the first time in association with mango tissues in Mexico. This study represents the first report of C. alienum causing mango anthracnose worldwide. The distribution of Colletotrichum species varied among the mango growing states from Mexico. Chiapas was the only state in which all five species were found. Pathogenicity tests on mango fruit cultivar Manila showed that all Colletotrichum species from this study could induce anthracnose lesions. However, differences in virulence were evident among species. C. siamense and C. asianum were the most virulent, whereas C. alienum and C. fructicola were considered the least virulent species.